Pengaruh Motivasi Kerja, Disiplin Kerja dan Insentif Terhadap Kepuasan Kerja Karyawan - Febrian Enriko Febrian Enriko; Tezar Arianto ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
This study aims to determine the effect of work motivation, work discipline, incentives on job satisfaction of employees of PT Citra Mitra Sehati Bengkulu. This type of research uses a causal associative method with a quantitative approach with a total sample of 75 employees. Data collection techniques used are observation, interviews, questionnaires. The data analysis method used is multiple linear regression, coefficient of determination, f test and t test.            The results of this study indicate that from the results of data management, it can be concluded that all independent variables, namely Work Motivation (X1), Work Discipline (X2) and Incentives (X3) variables simultaneously or jointly have a positive and significant effect on the dependent variable, namely Job Satisfaction. Employee (Y) at PT. Mitra Sehati image from the regression equation test results obtained are as follows: Y= 2.210 + 0.977 X1 + 0.406 X2 + 0.251 X Keywords : Work Motivation, Work Discipline, Incentives, Job Satisfaction